(untitled) (MAUSAM, 2016)
The present study was undertaken to analyze annual average rainfall in Gujarat in order to classify and define the targeted zones and to know the impact of rainfall variability on agriculture in the state. The results revealed that the Northwest Agro-climatic zone was the most vulnerable zone among all the agro-climatic zones due to extreme deviations in rainfall pattern. This was followed by north Saurashtra, South saurashtra and Middle Gujarat Zone. The southern hills zone had the least per cent of years with extreme deviations. Water management practices such as drip irrigation, deepening wells, constructing check-dams; integrated watershed management as well as insurance coverage and microfinancing facilities have been suggested as mitigation strategies to overcome the adverse impact of rainfall variability on agricultural production.